Treatment of tobacco dependence among HIV-infected patients: rationale and preliminary actions taken in Poland - Janik-Koncewicz, Kinga; Szetela, Bartosz; Gąsiorowski, Jacek; Jabłonowska, Elżbieta; Knysz, Brygida; Wójcik-Cichy, Kamila; Herbeć, Aleksandra; Zatoński, Witold (Journal of Health Inequalities, 2017)
Tobacco smoking and non-communicable diseases related to tobacco use are currently the most important health challenges in population of HIV positive patients, also in Poland. Treatment of tobacco dependence in HIV-infected individuals is now emerged as one of the most important areas for clinical care. One of the rationale for intensifying smoking cessation efforts in HIV population comes from epidemiological observations suggesting that tobacco smoking is responsible for 7 years of life lost in HIV-infected smokers. The Health Promotion Foundation in collaboration with the HIV specialised medical society in Poland has launched a multi-component programme aimed at reducing the prevalence of tobacco smoking in HIV population at least by half in the next years. The programme involves several activities: (1) research aimed at characterising the smoking epidemic among HIV positive patients in Poland; (2) assessment and capacity building in smoking cessation among healthcare professionals who treat HIV patients; as well as (3) formulation of recommendations for a comprehensive nationwide programme of tobacco dependence treatment in this group of patients in Poland.